Biohydrogen production by a microbial consortium isolated from local hot spring - Hasmoni, Siti Halimah (2018)
Biohydrogen production from microorganism is a form of renewable energy that could supplement the depletion of fossil fuels. In producing biohydrogen, microbial consortia are more feasible than pure cultures because of its operational ease and stability and it is more favourable energetically at elevated temperatures which enables thermophiles to reach higher biohydrogen production than mesophiles. The aim of this study was to isolate, enrich and screen microbial consortium from local hot spring for its potential in producing biohydrogen, to optimize the selected consortium for optimal biohydrogen production and to identify the microbial diversity community of the consortium. Sampling was conducted at Gadek, Cherana Putih, Gersik and Selayang hot spring and the samples were enriched in Mineral Salt Succinate medium. The enriched consortia were screened for biohydrogen production using Gas Chromatography-Thermal Conductivity Detector (GC-TCD) and the biohydrogen production of the selected consortium was optimized by one factor at a time (OFAT) method. The kinetic analysis of the growth and biohydrogen production of the consortium were analyzed using the modified Logistic growth equation and modified Gompertz equation respectively. The microbial diversity community of the consortia were observed using 16S rRNA polymerase chain reaction-denaturing gradient gel electrophoresis (PCR-DGGE). To determine the microbial population dynamics of the consortia, 16S rRNA clone library were constructed for the consortia before and after optimization and sequencing data were analyzed using Mothur. Microbial consortium from Gadek hot spring (GDC) yielded the highest biohydrogen production compared to other consortia. The optimized condition (15% (v/v) inoculum size, 50°C, pH 7, 2 g/L sodium pyruvate and 0.5 g/L tryptone) showed a maximal biomass growth of 0.563 g dry cell weight/L and apparent specific growth rate of 0.959 h-1. Whilst the optimized hydrogen production potential was 86.2 mmol H2/L culture with the maximal production rate of 4.117 mmol/L h-1, biohydrogen yield obtained was 135.7 mmol H2/g biomass and the lag phase time was 5.1 hours. DGGE showed a slight microbial shift between the consortia before and after optimization. From the 16S rRNA clone library, 21 clones were obtained and a total of four operational taxonomic unit (OTU) were detected. Both consortia showed Firmicutes and Proteobacteria as the predominant phyla which have phylogeny affiliations to hydrogen producers. However, OTU_4 (Sporoacetegenium mesophilum) was only present in the consortium before optimization, OTU_1 (Thauera sp), OTU_2 (Paenibacillus barengoltzii) and OTU_3 (Sporomusaceae g. sp) were present in both consortia. Analysis showed the presence of OTU_2 and OTU_3 and the abundance of OTU_1 in the optimized consortium led to an increased in biohydrogen production of about 8 fold more from the consortium before optimization. In conclusion, this is the first study that reports a unique combination of Thauera sp., Paenibacillus barengoltzii and Sporomusaceae g. sp. which are able to produce a high amount of biohydrogen at the optimized condition.